If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(y + -1) + -1(3y + -1) = 2y + -1 + -1(2y + 1) Reorder the terms: 3(-1 + y) + -1(3y + -1) = 2y + -1 + -1(2y + 1) (-1 * 3 + y * 3) + -1(3y + -1) = 2y + -1 + -1(2y + 1) (-3 + 3y) + -1(3y + -1) = 2y + -1 + -1(2y + 1) Reorder the terms: -3 + 3y + -1(-1 + 3y) = 2y + -1 + -1(2y + 1) -3 + 3y + (-1 * -1 + 3y * -1) = 2y + -1 + -1(2y + 1) -3 + 3y + (1 + -3y) = 2y + -1 + -1(2y + 1) Reorder the terms: -3 + 1 + 3y + -3y = 2y + -1 + -1(2y + 1) Combine like terms: -3 + 1 = -2 -2 + 3y + -3y = 2y + -1 + -1(2y + 1) Combine like terms: 3y + -3y = 0 -2 + 0 = 2y + -1 + -1(2y + 1) -2 = 2y + -1 + -1(2y + 1) Reorder the terms: -2 = 2y + -1 + -1(1 + 2y) -2 = 2y + -1 + (1 * -1 + 2y * -1) -2 = 2y + -1 + (-1 + -2y) Reorder the terms: -2 = -1 + -1 + 2y + -2y Combine like terms: -1 + -1 = -2 -2 = -2 + 2y + -2y Combine like terms: 2y + -2y = 0 -2 = -2 + 0 -2 = -2 Add '2' to each side of the equation. -2 + 2 = -2 + 2 Combine like terms: -2 + 2 = 0 0 = -2 + 2 Combine like terms: -2 + 2 = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 4x+-21x=91 | | x+5/3=2x-5/6 | | f(x)=x^3-7x^2+7x+15 | | w+(2w-4)+w+(2w-4)=46 | | 0.25-0.5=0.05 | | 7x^2-42=35x | | 3t+9=33 | | 9-9=12x+11x | | 8.2x-5=0 | | .50x+.4x=18 | | -60+2.5x=0 | | 16+t=-182 | | 15-4x=7-5x | | .10x+.25(x+4)+.05*5(x+4)=3.20 | | x+2y=zforx | | 3+4x+2x=12+4x-3x | | 4(1+6m)-8=-124 | | 3x+45=8x-220 | | 36=-9t | | 0=12m | | 21x^2+2x-.09=0 | | cos(x)=-05 | | (2xy)(3x^2y)= | | -84x^2+91x-7=0 | | 4y=8+3x | | (x^2-5)(5x)(-.25)= | | (n-2)180=108n | | 7(14a+7w)8(7a+9w)= | | (4+n)+(3n-7)i=8-2i | | x+4x+3=17 | | 2x+7y=27 | | 20=B/-0.2 |